Tax Socialization and Assistance in Kademangan, Muaro District, Jambi - Wiwik Tiswiyanti; Riksy Hernando; Eko Prasetyo (Indonesian Journal of Society Development, 2023)
The service aims to help partners understand aspects of taxation, especially village treasurers, regarding the village funds used. The tax socialization carried out in Kademangan Village relates to income tax, value added tax, treasurer's tax. With this socialization, it is hoped that the implementation of tax obligations in Kademangan Village can be carried out well again so that the government's efforts to achieve state revenue from the taxation sector can be achieved. As a result of the service carried out by the team in Kademangan Village, in general village officials have carried out tax obligations related to deductions/collections and deposits. Guidance on how to fill out a Tax Payment Letter (SSP) and Notification Letter (SPT) regarding tax withheld/collected. Provide assistance to submit Notification Letters online which has not been done by the Village Treasurer